PERFORMANCE MANAGEMENT TRANSFORMATION OF BATIK INDUSTRY IN MADURA USING HRIS - Akh Jalal; Fajar Wirahadi Kuncoro; As'adi Khas; Iriani Ismail (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2023)
This study aims to describe the concept, design, potential implications and challenges of using HRIS in the performance management of the Madura batik industry. This study used the literature study method, with data collection using editing, organizing, and founding techniques, with data analysis techniques using data reduction techniques, data presentation and taking conclusions. The results of this study indicate that HRIS can be applied to manage the performance of the Madura batik industry, taking into account aspects of the needs and budget of the batik industry in choosing and using HRIS optimally. In addition, there are several potential implications and challenges in the use of HRIS that need to be addressed by the Madura batik industry in developing industrial performance.